Excess reserves and monetary policy tightening - Fricke, Daniel; Greppmair, Stefan; Paludkiewicz, Karol (Review of Finance, 2026)
Abstract We show that the transmission of a monetary policy tightening varies in the cross-section of banks when central bank reserves are abundant. Specifically, the net worth of reserve-rich banks may display a boost when the interest rate paid on reserves increases strongly. Focusing on the European Central Bank’s 2022 rate hiking cycle, we show that reserve-rich banks’ credit supply is less sensitive to the monetary policy tightening compared to other banks. The effect varies in the cross-section of both banks and firms. The results are binding at the firm level, indicating the presence of real effects.